Mastering Globalization. - LACHAPELLE (Taylor & Francis Ltd., 2005)
Contemporary globalization is transforming and undermining the role of the nation-state, causing it to lose its grip on both the national economy and identity. This is a penetrating analysis" "of this phenomenon and an explorationn of how governments - national, regional, local, global city-regions - can respond. This original selection of essays discusses the impact of globalization on nation-states and the international system, the consequent political and sociological fragmentation of nations, and the rise of multiple identities within those nations. These essays uniquely investigate the dr.